(untitled) (Journal of Engineering, 2012)
The present study focused mainly on the buckling behavior of composite laminated plates subjected to mechanical loads. Mechanical loads are analyzed by experimental analysis, analytical analysis (for laminates without cutouts) and numerical analysis by finite element method (for laminates with and without cutouts) for different type of loads which could be uniform or non-uniform, uniaxial or biaxial. In addition to many design parameters of the laminates such as aspect ratio, thickness ratio, and lamination angle or the parameters of the cutout such as shape, size, position, direction, and radii rounding) which are changed to studytheir effects on the buckling characteristics with various boundary conditions. Levy method of classical laminated plate theory and Finite element coded by ANSYS 13.0 is used to formulate the theoretical model. Results are compared with other researches and good agreement was obtained.